Effects of Chalcone Derived Compounds on Cell Cycle and Migration Capability of Human Breast and Lung Cancer Cells - Avci, H.; Altintas, H. Gunduz; Yildiz, Y.; Coskun, D.; Ari, F. (Pleiades Publishing Inc, 2023)
We aimed to investigate the anticancer activity of new synthesis benzofuran-substituted chalcone derivatives, which have the potential to be chemotherapeutic agents, in lung and breast cancer cell lines. The cytotoxic effect of chalcone derivatives on cell viability was determined by ATP (48 h) viability test. Doses of compounds found to be toxic to cell viability were examined using fluorescent staining (Hoechst and Propidium Iodide (PI)) to determine the mode of cell death (apoptosis and necrosis). After examining the effects of the compounds on the cell death mode, their effects on the migration abilities by the wound healing method were investigated. The effects of benzofuran chalcone derivative compounds on cell cycle were also investigated in lung and breast cancer cell lines. Two chalcone-derived compounds (Compound 1 and Compound 2) exhibited a potent anti-growth effect on lung cancer (A549 and H1299) and breast cancer (MCF-7 and MDA-MB-231) cell lines. In the double staining used to assess cell mode, the amount of PI positive cells increased with increasing dose, as did the number of pycnotic and fragmented nuclei, both of which are apoptotic markers. The compounds have been found to limit the migration capacity of cells. Finally, two chalcone-derived compounds inhibit the division of lung and breast cancer cell lines by keeping them in the G2/M phase of the cell cycle. Considering these promising results, we can say that advanced analyzes are required for the development of these two chalcone-derived chemicals as anticancer agents.
Keywords: breast cancer; lung cancer; chalcone derivatives; cytotoxicity